LEGITIMASI HEGEMONI HUKUM ADAT DALAM KARYA SASTRA BERLATAR KULTURAL BALI - Dwipayana, I Kadek Adhi; Adnyana, Ida Bagus Gede Bawa (Universitas Hasanuddin, 2019)
AbstractThis article talks about the legitimacy of Balinese customary law and the reinterpretation of the authors of Balinese customary law in cultural literary works. Theoretically, this research has an urgency in the development of science, especially the knowledge of literary discourse, while practically providing understanding to the public about Balinese customary law and how to address the cultural problems of the people in Bali. This study used a descriptive qualitative research design that moved from a functional approach to Balinese cultural literary works. The primary data sources of this research are a collection of